Variovorax terrae sp. nov. Isolated from Soil with Potential Antioxidant Activity - Woo, Chae Yung; Kim, Jaisoo (Journal of microbiology and biotechnology, 2022)
A white-pigmented, non-motile, gram-negative, and rod-shaped bacterium, designated CYS-02 T , was isolated from soil sampled at Suwon, Gyeonggi-do, Republic of Korea. Cells were strictly aerobic, grew optimally at 20-28℃ and hydrolyzed Tween 40. Phylogenetic analysis based on 16S rRNA gene sequence indicated that strain CYS-02 T formed a lineage within the family Comamonadaceae and clustered as members of the genus Variovorax. The closest members were Variovorax guangxiensis DSM 27352T (98.6% sequence similarity), Variovorax paradoxus NBRC 15149 T (98.5%), and Variovorax gossypii JM-310 T (98.3%). The principal respiratory quinone was Q-8 and the major polar lipids contain phosphatidylethanolamine (PE), phosphatidylethanolamine (PG), and diphosphatidylglycerol (DPG). The predominant cellular fatty acids were C 16:0 , summed feature 3 (C 16:1 ω7c and/or C 16:1 ω6c) and summed feature 8 (C 18:1 ω7c and/or C 18:1 ω6c). The DNA GC content was 67.7 mol%. The ANI and dDDH values between strain CYS-02 T and the closest members in the genus Variovorax were ≤ 79.0 and 22.4%, respectively, and the AAI and POCP values between CYS-02 T and the other related species in the family Comamonadaceae were > 70% and > 50%, respectively. The genome of strain CYS-02 T showed a putative terpene biosynthetic cluster responsible for antioxidant activity which was supported by DPPH radical scavenging activity test. Based on genomic, phenotypic and chemotaxonomic analyses, strain CYS-02 T was classified into a novel species in the genus Variovorax, for which the name Variovorax terrae sp. nov., has been proposed. The type strain is CYS-02 T (= KACC 22656 T = NBRC 00115645 T ).